2011
DOI: 10.1097/rct.0b013e31823421ac
|View full text |Cite
|
Sign up to set email alerts
|

Can the Patient With Cirrhosis Be Imaged for Hepatocellular Carcinoma Without Gadolinium?

Abstract: Non-gadolinium-enhanced MRI had a moderate sensitivity for HCC but had a high specificity. Although non-gadolinium-enhanced MRI cannot be recommended as a primary imaging approach for HCC, the results demonstrate the contribution of non-gadolinium-enhanced sequences to imaging of HCC. A non-gadolinium-enhanced MRI protocol may have a diagnostic value when gadolinium cannot be administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…SWI showed a sensitivity, accuracy, and PPV of 84.4% and 84.4%, 85.4% and 83.8%, 98.5% and 98.2% for lesion-based and patient-based analysis, respectively. This was consistent with the study by Hardie et al They found that T2*WI had a sensitivity and specificity of 60% and 100% for identifying HCC and a greater degree of liver iron deposition allowed for increased conspicuity of HCC [ 34 36 ]. However, it was not confirmed by iron-staining pathologic correlation.…”
Section: Discussionsupporting
confidence: 91%
“…SWI showed a sensitivity, accuracy, and PPV of 84.4% and 84.4%, 85.4% and 83.8%, 98.5% and 98.2% for lesion-based and patient-based analysis, respectively. This was consistent with the study by Hardie et al They found that T2*WI had a sensitivity and specificity of 60% and 100% for identifying HCC and a greater degree of liver iron deposition allowed for increased conspicuity of HCC [ 34 36 ]. However, it was not confirmed by iron-staining pathologic correlation.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the total examination time was about 10 minutes only. A previous study performed in the late 2000s reported modest sensitivity (52–55%) and high specificity (88–90%) of non-contrast MRIs compared to contrast-enhanced MRIs (sensitivity, 81–84%; specificity, 62–65%) in liver transplantation patients ( 28 ). However, according to Kim et al ( 10 ) in 2013, the sensitivity (91.2–95.1%) and specificity (66.7–79.4%) of non-contrast MRIs are comparable to those of contrast-enhanced MRI (sensitivity, 93.9–95.9%; specificity, 75.7–82.4%).…”
Section: Discussionmentioning
confidence: 98%
“…Hardie et al reported that non-contrast MRI has moderate sensitivity for HCC detection in transplanted liver compared to gadolinium-enhanced MRI (53.5% vs 82.5%), implying diagnostic value of non-contrast MRI when gadolinim cannot be administered. 23 In a study which analyzed patients who underwent surgical resection, Kim et al reported that the Az value of the non-contrast MRI (mean, 0.906) was not inferior to that of the gadoxetic acid-enhanced whole MRI (mean, 0.924) for detecting HCC and cholangiocarcinoma (p > 0.05). 24 The previous study 24 and our current study both demonstrated considerably high sensitivity of non-contrast MRI for detecting HCC (92.2-93.0% and 97.0%, respectively).…”
Section: Discussionmentioning
confidence: 99%